PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT UNTUK MENINGKATKAN HASIL BELAJAR IPA SD NEGERI 163 TELLULIMPOE - Sudarto, Sudarto; Adnan, Adnan; Andi Nirwana (Jurnal Cakrawala Ilmiah, 2024)
This research is motivated by the implementation of the Teams Games Tournament Type Cooperative Learning Model to Improve the Science Learning Outcomes for the V Students at SD Negeri 163 Tellulimpoe, Majauleng District, Wajo Regency. This type of research is a classroom action research conducted in the V of SD Negeri 163 Tellulimpoe with a totaly of 16 students as subjects consisting of 8 boys and 8 girls. Data collection techniques in this research used an observation and tests. The data analysis technique used in this research is a quantitative. Based on the results of this research that has been carried out, the student learning outcomes increase through the implementation of the teams games tournament type cooperative learning model. This can be seen from the percentage of completeness of student learning outcomes of 62.5% in cycle I, to 81.25% in cycle II, an increase of 18.75%. Thus, it can be concluded that the application of the team games tournament type cooperative learning model can improve learning outcomes in science subjects for fifth grade students at SD Negeri 163 Tellulimpoe